2019
DOI: 10.1002/jcla.22895
|View full text |Cite
|
Sign up to set email alerts
|

Delta neutrophil index as a prognostic marker in emergent abdominal surgery

Abstract: BackgroundDelta neutrophil index (DNI) is the fraction of circulating immature granulocytes provided by a routine, complete blood cell analyzer. It is known to be a useful prognostic marker of sepsis. The aim of this study was to evaluate the role of DNI in the diagnosis and prognosis of patients who had undergone emergent surgery for an acute abdomen.MethodsA total of 694 patients who had visited the emergency room for acute abdominal pain and undergone emergent abdominal surgery from May 2015 to September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…[ 33 ] In particular, studies conducted in the surgical field have shown that DNI could be useful for predicting disease severity, the necessity of surgical intervention, and prognosis. [ 11 , 15 17 , 34 , 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] In particular, studies conducted in the surgical field have shown that DNI could be useful for predicting disease severity, the necessity of surgical intervention, and prognosis. [ 11 , 15 17 , 34 , 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…60 studies were finally excluded according to the exclusion criteria: not relevant to GI diseases (n = 42), pediatric study (n = 11), abstract only study (n = 2), animal study (n = 2), study protocol (n = 1), and systematic review or meta-analysis (n = 2). The remaining 12 articles [9,[17][18][19][20][21][22][23][24][25][26][27] were included in the systematic review. Among the 12 studies, Kim JW et al [22] explored the prognostic role of DNI measured at admission day 3, and the results of the study by Cha YS et al [26] cannot be extrapolated as a form of TP, FP, FN, or TN (although we contacted corresponding author, we could not get the crude numbers of TP, FP, FN, or TN).…”
Section: Study Selectionmentioning
confidence: 99%
“…Among the 12 studies, Kim JW et al [22] explored the prognostic role of DNI measured at admission day 3, and the results of the study by Cha YS et al [26] cannot be extrapolated as a form of TP, FP, FN, or TN (although we contacted corresponding author, we could not get the crude numbers of TP, FP, FN, or TN). Therefore, these two publications were excluded in the quantitative analysis, and a total of 10 studies [9,[17][18][19][20][21][23][24][25]27] were included in the meta-analysis of diagnostic test accuracy. Figure 1 presents a flow diagram showing the process for identifying the relevant studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the cellular biomarkers, delta neutrophil index (DNI) is well documented as a beneficial marker in determining the occurrence of candidemia [ 10 ] with systemic inflammatory response syndrome (SIRS) and a marker of disease severity in sepsis patients [ 11 , 12 , 13 ]. DNI via an automatic hemanalyzer is easily calculated by the cellular formula of delta neutrophil index = (neutrophil [%] + eosinophil [%] − polymorphonuclear neutrophil [PMN][%]).…”
Section: Introductionmentioning
confidence: 99%